PERSEPSI PETANI TERHADAP PENTINGNYA PERAN PENYULUHAN PADA PETANI GAMBIR DIKECAMATAN PANGKALAN KOTO BARU KABUPATEN LIMAPULUH KOTA PROVINSI SUMATERA BARAT - Sutrisno, Sutrisno; Sayamar, Eri; Kausar, Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The success of extension is not separated from the importance of the extension role that has been implemented. One of the roles of extension is to facilitate the learning process of main actors (perpetrators of agricultural activities) and business people as well as seek access to key actors and business people to source information, technology, and other resources to They can develop their business, therefore the extension can be held well not regardless of the importance of the extension role in achieving the purpose of the extension itself. In addition, the importance of the counseling role is carried out to develop knowledge, attitudes, and skills for the main actors and businesses in carrying out their daily activities on gambir plantation activities. How the perception of extension to the importance of the counseling role in the Gambir plant in the district of Pangkalan Koto Baru District Lima Puluh Kota regency of West Sumatra Province is very interesting to be examined according to the background above. This research aims to know the implementation of extension in the gambir plant in the district of Pangkalan Koto Baru Lima Puluh Kota regency, and know the perception of farmers to the importance of the extension role in the Gambir plant in Pangkalan  Koto Baru District Lima Puluh Kota regency province of West Sumatra. This research uses the survey method. Data is collected in a descriptive and qualitative through direct observation. The results of this research showed that the extension role in the subdistrict of new district is in the category of role with the average score of 3.59 (role).Keywords : Perception, Extension role, Farmer